Quality Control of PCC (Portland Composite Cement) Using the Six Sigma Method at PT. XY - Achmad Syarifudin; Sri Ndaru Arthawati; Sri Mukti Wirawati; Pugy Gautama (AGUSPATI Research Institute, 2026)
PT. XY is a premium cement manufacturer producing Portland Composite Cement (PCC) and Ordinary Portland Cement (OPC). Throughout 2023, the company’s production line experienced recurring defect problems, including cement contaminated by water, weighing scale non-compliance with Standard Operating Procedures (SOP), and brittle cement quality. These conditions led to a decline in customer satisfaction while simultaneously increasing production costs. This study applies the Six Sigma approach with the DMAIC (Define, Measure, Analyze, Improve, Control) framework to identify, measure, and minimize defect rates. Data collection was conducted from January to December 2023 at the Quality Control Laboratory of PT. XY, Ciwandan Plant, Cilegon, Banten. The analysis revealed 83,523 defective sacks out of a total of 432,751 sacks produced. The Defects Per Million Opportunities (DPMO) value obtained was 64,334.9, equivalent to a sigma level of 3, indicating that the production process is at an average industrial level and still requires significant improvement. The most dominant defect type was scale non-compliance with SOP (38.23%), followed by brittle cement quality (31.08%) and cement exposed to water (30.69%). Through fishbone diagram analysis, the primary causal factors were identified across categories of human, machine, method, material, and environment. Specific improvement recommendations for each defect category are proposed to drive the sigma level toward a higher stage.